2009
DOI: 10.18352/bmgn-lchr.123
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of upstream and downstream resource managers to engage in compensation schemes for environmental services

Abstract: Providing compensation for land conservation practices adopted by upstream farmers is still an alien concept in the Thai political context. The governance of common-pool natural resources, such as forest and water, has traditionally been under the control of powerful government line agencies, while the contribution of local communities to natural resource conservation have been hardly recognized by policy-makers. Drawing on a case study in Mae Sa watershed, Chiang Mai province, northern Thailand, this paper di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The age and education level of the household heads in the downstream communities were positively correlated with a willingness to pay for an improvement in water resources, and farm households with high acreages and with rice as their main crop were also more likely to participate in a compensation scheme. The research also showed that having a high proportion of non-farm income negatively affected households' willingness to pay, which is of major significance for the design of future PES schemes given the decreasing contribution of agriculture to rural people's incomes in less remote areas (Sangkapitux et al 2009). …”
Section: Identification Of the Pes Marketmentioning
confidence: 96%
See 4 more Smart Citations
“…The age and education level of the household heads in the downstream communities were positively correlated with a willingness to pay for an improvement in water resources, and farm households with high acreages and with rice as their main crop were also more likely to participate in a compensation scheme. The research also showed that having a high proportion of non-farm income negatively affected households' willingness to pay, which is of major significance for the design of future PES schemes given the decreasing contribution of agriculture to rural people's incomes in less remote areas (Sangkapitux et al 2009). …”
Section: Identification Of the Pes Marketmentioning
confidence: 96%
“…An interesting finding of this study was that poorer groups among the upstream resource managers were more likely to engage in compensation schemes for ecological services, because payments would provide a rather secure and regular benefits stream, and that the establishment of such schemes would likely improve their tenure security in this protected watershed area. Willingness to accept compensation for the adoption of environment-friendly practices was also found to be positively influenced by the age and education of the respondents and their previous experiences with on-site soil erosion, water shortages and drought (Sangkapitux et al 2009). Another study in the Mae Sa watershed by Punyawadee et al (2010) found that downstream water users showed a marginal willingness to pay an additional 40-90 % of their monthly tap water fees for clean, non-chemical contaminated drinkable water.…”
Section: Identification Of the Pes Marketmentioning
confidence: 98%
See 3 more Smart Citations